ANALISIS PENGARUH KEUNGGULAN PRODUK, KEGUNAAN PRODUK DAN PROMOSI TERHADAP TINGKAT KESUKSESAN PRODUK TELKOM FLEXI DI JEPARA - Nurul Komaryatin; Fitri Ella Fauziah (Universitas Islam Nahdlatul Ulama Jepara, 2006)
AbstractThis research aim to test influence of usefulness of product, excellence of product and promotion to level successfulness of product of telkomjlexi with research location in Jepara and period of research executed in the year 2004 2005. Population at this research is] customer of telkomjlexi (Jlexi trendy and classy). Sampling technique use approach of non-probability sampling, that is accidental sampling, while amount of taken sampel counted 97 responder Data type is primary and sekunder data and collected with documentation and kuesioner Its Analysis technique with linear regression analysis. Test of quality data (validity and reliability) and test classic assumption is conduct to ascertain goodness-offt model regresi.Result of data analysts show that third variable (usefulness of product, excellence of product and promotion) hax'e positive influence and signifikan to level successfulness of product of Telkomjlexi, either through and also parsial of simultan. Variable sequence pursuant to strength of its influence is excellence of product (strongest) later then promotion and usefulness of product Keyword : usefulness of product, excellence of product, storey;level and promotion successfulness of new product.